Outros Sísifos - Miguel Filipe Mochila (Carnets)
The attachment of Vergílio Ferreira to a «problem-novel» with a philosophical theme, focusing on the existential question, finds in Albert Camus a natural referent. Under the sign of the Hegelian unhappy consciousness, a problematic is developed according to which the human being senses through flashes, the pathetic discrepancy between the actual plane where he moves and that other, the ideal plane, that is projected in his various experiences of the world. The problematic of how to be in his being, in its form, heideggerian, a being-towards-death, routes the difficult clarification between a poetics of hope in the revelation of meaning and the encounter of man with himself, a march from the real plane to the ideal plane that mobilizes him, and the absolute assurance of its failure pointing directly to his heart in a maelstrom of nothingness. Both works reveal the paradoxical dimension of the subject that envelop him as a momentum for anguish.